Resilience in higher education: A conceptual model and its empirical analysis - Durso, Samuel de Oliveira; Afonso, Luís Eduardo; Beltman, Susan (Education Policy Analysis Archives, 2021)
This research analyzes how the resilience of higher education students is shaped during the undergraduate program by personal and contextual factors. In this research, the resilient student is one who faces a high burden of stress and/or adversity during their undergraduate course but manages to reach the end of the program satisfied and/or committed to the chosen career. Based on the literature review, we developed the Academic Resilience Model (ARM), which explains the sources of stress and/or adversity, as well as the protective mechanisms and/or factors that affect students throughout the program. We empirically test this model by conducting a phenomenology-based qualitative study at a public university in Brazil. The results of ARM validation indicate that the main sources of stress and/or adversity and protective mechanisms and/or factors come from individual, academic and external systems. Examples of sources of stress/adversity were the low initial motivation for the program, personal health problems, faculty didactic-pedagogical deficiency, difficulties in relationships with peers, and competing professional demands. On the other hand, the main protective mechanisms/factors identified were the capacity of adaptability, self-control, personal organization, good relationships with the faculty, integration with peers, and support of family. The research enabled identification of how resilience helps students to overcome barriers in higher education, generating important results for future education policies.